2019
DOI: 10.1093/eurheartj/suz208
|View full text |Cite
|
Sign up to set email alerts
|

My life with pulmonary arterial hypertension: a patient perspective

Abstract: In recent years, there has been an increase in therapeutic options and treatment strategies for pulmonary arterial hypertension (PAH). However, patients still report delays in receiving a diagnosis, which is a significant burden associated with the disease, and which shows a general lack of disease awareness. This review has been written by two PAH patients to describe the patient experience and explore the ways in which patients are increasingly being given a voice in developing approaches to treatment. As pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…Conversely, in CG participants significant deterioration was confirmed exactly on the AO subscale. These results mirror data from studies on the perspective of patients with PH that described the need to organize and plan daily life, pay attention to physical and emotional well-being and follow a routine of sleep and diet [ 4 , 31 ]. Besides, Rawling et al (2020) in the synthesis of qualitative studies on the experience of adult patients living with PH described four main topics, one of which emphasized the transitional nature of PH.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Conversely, in CG participants significant deterioration was confirmed exactly on the AO subscale. These results mirror data from studies on the perspective of patients with PH that described the need to organize and plan daily life, pay attention to physical and emotional well-being and follow a routine of sleep and diet [ 4 , 31 ]. Besides, Rawling et al (2020) in the synthesis of qualitative studies on the experience of adult patients living with PH described four main topics, one of which emphasized the transitional nature of PH.…”
Section: Discussionsupporting
confidence: 65%
“…Recognizing that social participation, for example, meeting friends, volunteer work, club activities, and quality of social relationships, described as sense of belonging, respect, inclusion, are important predictors of well-being in persons living with long-term health problems [ 32 ], interventions to support participation are highlighted as relevant part of the interdisciplinary treatment approach. Furthermore, note that studies of the patient’s perspective [ 3 , 4 ] agree that patients with PAH often describe feeling insecure, isolated, and as living with an invisible disease, therefore, to fully eliminate the impact of PAH on a patient’s life, complex interventions in addition to medical treatment of the underlying disease are important, and therefore our treatment approach has the potential to support an individual living with PAH to cope with illness. The observed benefits of the investigated program to improve the perceived chance of participation in activities related to frequency of social contacts in the PAH patients might be due to the change in the perception about their health condition and the improved sense of self-control abilities, as is approved relevant correlations between these factors in other studies [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PAH adversely affects patients’ quality of life regardless of age 12–14 and being mindful of its impact on patients’ daily lives can be particularly important when treating elderly patients, for whom maintenance or improvement of quality of life may be the main treatment goal. Few studies have investigated patient-reported outcomes in elderly PAH patients but a separate review in this supplement 15 is devoted to the patient’s perspective and discusses measures to improve disease management in more detail.…”
Section: Introductionmentioning
confidence: 99%
“…By sharing their journey, their fears but also their hopes and their trust in the future, we believe that the testimony of our patients will touch the heart and soul of our readers. We are together united to fight for them and with them, against this condition, which we hope, one day, will be cured 17 …”
mentioning
confidence: 99%